First Principle Investigations Of Hydrogen Adsorption In Metal Organic Framework-5 - Hussim, Muhammad Hafiz (2013)
Computational molecular-orbital study had been conducted to find the binding energy and binding position of Metal Organic Frameworks – 5 (MOF – 5) for hydrogen molecules adsorption. Five model molecules (model molecule M1 to M5) for MOF-5 were investigated to find the effects of the 1,4-Benzenedicarboxylate (BDC) linker coordination and dangling bonds terminator scheme on the binding energy and the binding position of the absorbed hydrogen. In the initial stage study, we had performed the calculations using the Density Functional Theory method to determine the binding position and binding energy of hydrogen molecule near the BDCLi2 molecule. This method with HCTH functional at 6-31G(d) basis sets was chosen as the procedure for all calculations of binding energy and binding position of four binding sites namely the α, β, g, and d sites both in the perpendicular and parallel orientation of the hydrogen molecule. The higher order basis sets were found to provide more accurate results but with higher computational cost. It was found that the BDC linker coordination and dangling bonds terminator scheme do affect the binding energy of the hydrogen molecules at the β and g sites of the MOF-5 model molecules. Model molecule M5 was tested for multiple hydrogen molecules adsorption using partial optimization method.